Development of a Digital Marketing Strategy to Increase Market Share for Local Cosmetic Products - Nugroho, Dony Ari (Ridwan Institute, 2024)
This research aims to understand the development of effective digital marketing strategies in improving the competitiveness of local cosmetic products in the digital market. The method used in this research uses qualitative research methods. Data collection to obtain information related to the topic was conducted through literature study. Through the evaluation of various strategies, including social media marketing, online advertising, SEO, and content marketing, this research highlights the importance of an integrated and customised approach to brand needs. The results show that implementing the right strategies can bring significant positive impacts, including increased brand visibility, consumer awareness, and sales of local cosmetic products. With a deep understanding of consumer preferences and the digital market environment, stakeholders in the cosmetics industry can take strategic steps to expand their market share and achieve long-term success in this rapidly changing environment.